The dialectic of life and death in the texts of Ghazi (Azrael play - a choice) (Al-Academy, 2024)
The research deals with the dialectic of life and death in the texts of Mithal Ghazi (the play Azrael - Ikhtiyaran) and its semantic implications. The dialectic of life and death is one of the existential issues that occupied a large space in philosophical thought. The presence of death means the absence of life, and the presence of life means the absence of death. In addition, the writer lives in loss and daily scenes of death in his social environment as a state and feeling, and what these scenes constitute of daily concerns that cast their shadows on the members of society. The dialectic of life and death is one of the important stations that constitute an obsession in the life of the ordinary person and the most present in his mind. According to this vision, the research was concerned with studying the dialectic of life and death in the texts of Mithal Ghazi. The first chapter included the research problem that defined the question: Was the author able to explain the nature of the dialectic of life and death in his theatrical texts? This study came to shed light on the dialectic of life and death in the play (Azrael). This study included the introduction to the research in which the research presented the problem of the research, its importance and its goal. Then the theoretical framework that dealt with the theoretical foundation of the research included two topics: the first: in the philosophy of life and death and the second: the dialectic of life and death in the global theatrical text. The research came out with a set of indicators that I relied on in analyzing the research sample model. After the analysis, the research came out with a set of results, including:1- The dialectic of life and death became clear in the research sample model through the defense of the woman's character for her existence in life and her insistence and refutation of the idea of death, while death represented the character of the man or Azrael who insisted on taking her soul and transferring it to the other world.2- The theatrical text indicated that all the social ties and relationships that a person practices are dialectically linked to the life of a person in this worldly life and cannot prevent death from any person.3- The sample model showed that the issue of a person's transition from the worldly life to the world of the afterlife or the isthmus is an inevitable result that no person can escape from